Regional implications of public investments and external shocks in Papua New Guinea: An economywide analysis - Dorosh, Paul A.; Fang, Peixun; Pradesha, Angga (International Food Policy Research Institute, 2025)
Improvements in telecommunications have enabled a tremendous increase in the flow of information across Papua New Guinea. Although transport costs remain high between various parts of the main island of Papua New Guinea, as well as between the main island and other parts of the country (e.g. the islands of New Britain and Bougainville to the East), phone and internet conditions enable government, traders and entrepreneurs to share market information that reduces transactions costs and improves market function. Nonetheless, there remain major differences in agricultural production, income sources and demand patterns across regions that are important to take into account in analyzing the impacts of external shocks and formulating development strategies.